Neoadjuvant Treatment in Rectal Cancer: Actual Status. (11th July 2011) - Garajová, Ingrid; Di Girolamo, Stefania; de Rosa, Francesco; Corbelli, Jody; Agostini, Valentina; Biasco, Guido; Brandi, Giovanni
Abstract : Neoadjuvant (preoperative) concomitant chemoradiotherapy (CRT) has become a standard treatment of locally advanced rectal adenocarcinomas. The clinical stages II (cT3-4, N0, M0) and III (cT1-4, N+, M0) according to International Union Against Cancer (IUCC) are concerned. It can reduce tumor volume and subsequently lead to an increase in complete resections (R0 resections), shows less toxicity, and improves local control rate. The aim of this review is to summarize actual approaches, main problems, and discrepancies in the treatment of locally advanced rectal adenocarcinomas.